2014
DOI: 10.13080/z-a.2014.101.016
|View full text |Cite
|
Sign up to set email alerts
|

Total, cold and hot water extractable organic carbon in soil profile: impact of land-use change

Abstract: The content of labile, especially water extractable organic carbon (WEOC) is a sensible indicator of soil organic matter quality. The main objectives of this study were: i) to investigate the profile changes of cold and hot water extractable organic carbon in forest and arable soils; ii) to evaluate the correlation between these labile fractions of soil organic matter and total organic carbon content. The experiments were carried out on a Gleyic Albeluvisol (ABg) in the upper part of Dniester basin, Western Uk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 22 publications
5
14
0
1
Order By: Relevance
“…In tilled soil under both crop production systems the assessed quantities of CWEC in all studied layers represented similar level and were two times higher as compared with non-tilled ( Figure 7). Our results are in accordance with the ones published earlier by Hamkalo and Bedernichek [30]. They also indicated that quantities of HWEC and CWEC were significantly lower in arable than in uncultivated soils.…”
Section: Effects On Water Extractable Carbon Fractionsupporting
confidence: 94%
See 1 more Smart Citation
“…In tilled soil under both crop production systems the assessed quantities of CWEC in all studied layers represented similar level and were two times higher as compared with non-tilled ( Figure 7). Our results are in accordance with the ones published earlier by Hamkalo and Bedernichek [30]. They also indicated that quantities of HWEC and CWEC were significantly lower in arable than in uncultivated soils.…”
Section: Effects On Water Extractable Carbon Fractionsupporting
confidence: 94%
“…In tilled soil under both crop production systems the assessed quantities of CWEC in all studied layers represented similar level and were two times higher as compared with non-tilled ( Figure 7). Our results are in accordance with the ones published earlier by Hamkalo and Bedernichek [30]. They The highest quantity of HWEC fraction was assessed in the surface soil depth 0-5 cm under permanent grass 1387.2 µg g −1 d.w. of soil, on average, which was almost three times the quantity obtained in soil under the CON system.…”
Section: Effects On Water Extractable Carbon Fractionsupporting
confidence: 93%
“…Pastaruoju metu vis daugiau kalbama ir tyrinėja ma, kaip biodujų gamybos procese likusios atliekos, panaudotos žemės ūkyje, tampa organinės anglies šaltiniu ir prisideda prie dirvožemių kokybės geri nimo. Vis daugiau dėmesio skiriama labiliajai dir vožemio angliai (Rao et al, 2013;Hamkalo et al, 2014), kuri pripažįstama kaip gero dirvožemio in dikatorius (Strosser, 2010;Dinesh et al, 2015). La biliosios anglies šaltiniai, nustatyti chemiškai frak cionuojant, pripažįstami kaip jautrūs dirvožemio organinės medžiagos kokybės ir sudėties pokyčių indikatoriai, vykstantys dėl dirvožemio naudojimo pokyčių (Landgraf et al, 2006;Šlepetiene et al, 2010).…”
Section: įVadasunclassified
“…The hot-water-dissolved C (HWDC) consists of more stable components that function as a reserve of nutrients and energy for plants and microorganisms (Bu et al 2011). Compared with the CWDC, the HWDC pool is bigger (5-to 10-fold) and represents a more heterogeneous C pool (Hamkalo and Bedernichek 2014). This is because hot (≥70°C) water kills vegetative cells of microorganisms and extracts many components from microbial biomass, as well as many nonmicrobial soil organic substances (Landgraf et al 2006).…”
Section: Introductionmentioning
confidence: 99%